Functional Brain Activity within the Medial and Lateral Portion of BA10 during a Prospective Memory Task - Francesco Barban; Giovanni Augusto Carlesimo; Emiliano Macaluso; Carlo Caltagirone; Alberto Costa (Behavioural Neurology)
In this study we tested the gateway hypothesis of Broadmann area 10 (BA10). With a functional magnetic resonance imaging (fMRI) protocol we manipulated the saliency–stimulus-oriented (SO) attending– and the memory load – stimulus-independent (SI) attending–during a prospective memory (PM) task. We found a significant main effect of the SO manipulation within the medial BA10 and a significant interaction between SI attending and PM task within the left lateral BA10. Our results give experimental support to the gateway hypothesis.